Further dismemberment of Discocyrtus with description of a new Amazonian genus and a new subfamily of Gonyleptidae (Opiliones, Laniatores) - Carvalho, Rafael; Kury, Adriano (European Journal of Taxonomy, 2018)
A group of Amazonian harvestmen is recognized and described as Amazochroma gen. nov. This taxon includes Discocyrtus carvalhoi Mello-Leitão, 1941 (type species), the only species of Discocyrtus previously thought to occur in Amazonia, and Amazochroma pedroi gen. et sp. nov., described here from the Brazilian states of Acre and Rondônia. New records are added for Amazochroma carvalhoi gen. et comb. nov, expanding its distribution from the Brazilian state of Mato Grosso northwards also to Pará and Amazonas in Brazil and additionally French Guiana and Suriname. Diagnostic features of Amazochroma gen. nov. include: trichromatic pattern of legs, dry marks on the dorsal scutum and base of legs and diastema in the row of macrosetae C of the penis ventral plate. A morphological maximum parsimony analysis (1022 scorings; 16 taxa; 64 characters) is performed to test whether Amazochroma gen. nov. is a member of Discocyrtus and if the traditional allocation of Discocyrtus in Pachylinae is defendable. A clade is retrieved containing three groups: (1) Mitobatinae, (2) Discocyrtus and (3) a clade containing Amazochroma gen. nov., Discocyrtanus and Roeweria, here described as a new subfamily of Gonyleptidae – Roeweriinae subfam. nov. Discocyrtanus Roewer, 1929 and Roeweria Mello-Leitão, 1923 are accordingly here transferred from Pachylinae to Roeweriinae subfam. nov.